2022
DOI: 10.1039/d1dt03323a
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid organic–inorganic triguanidine arsenate dihydrate for ultraviolet nonlinear optical application

Abstract: Introduction of the planar organic cation [C(NH2)3]+ into tetrahedronal inorganic arsenate generates a new ultraviolet nonlinear optical crystal triguanidine arsenate dihydrate, [C(NH2)3]3AsO4·2H2O, which showcase short ultraviolet absorption edge (210 nm),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…As shown in Figure 4a, the curve declined with a decrease in the wavelength, and the transmittance reached zero at 210 nm, suggesting that the UV cutoff edge of GZCO is 210 nm, which corresponds to the band gap of 5.9 eV. The cutoff edge of GZCO is quite close to those of reported guanidinium-based NLO compounds, such as [C(NH 2 ) 3 ]BF 4 (201 nm), 49 [C(NH 2 ) 3 ]SO 3 F (∼200 nm), 50 [C(NH 2 ) 3 ] 3 AsO 4 •2H 2 O (210 nm), 51 [C(NH 2 ) 3 ]SbF 4 (240 nm), 52 and [C(NH 2 ) 3 ] 6 (PO 4 ) 2 • 3H 2 O (205 nm). 53 In addition, the value is shorter than those cyanurates and melamine-based crystals such as KLi-(HC 3 N 3 O 3 ) (237 nm), 46 Ba 3 (C 3 N 3 O 3 ) 2 (241 nm), 61 2-(C 3 H 7 N 6 ) + •2Cl − •H 2 O (245 nm), 47 and (H 7 C 3 N 6 )(H 6 C 3 N 6 )-ZnCl 3 (236 nm).…”
Section: Differential Thermal Analysis and Thermogravimetricsupporting
confidence: 82%
See 2 more Smart Citations
“…As shown in Figure 4a, the curve declined with a decrease in the wavelength, and the transmittance reached zero at 210 nm, suggesting that the UV cutoff edge of GZCO is 210 nm, which corresponds to the band gap of 5.9 eV. The cutoff edge of GZCO is quite close to those of reported guanidinium-based NLO compounds, such as [C(NH 2 ) 3 ]BF 4 (201 nm), 49 [C(NH 2 ) 3 ]SO 3 F (∼200 nm), 50 [C(NH 2 ) 3 ] 3 AsO 4 •2H 2 O (210 nm), 51 [C(NH 2 ) 3 ]SbF 4 (240 nm), 52 and [C(NH 2 ) 3 ] 6 (PO 4 ) 2 • 3H 2 O (205 nm). 53 In addition, the value is shorter than those cyanurates and melamine-based crystals such as KLi-(HC 3 N 3 O 3 ) (237 nm), 46 Ba 3 (C 3 N 3 O 3 ) 2 (241 nm), 61 2-(C 3 H 7 N 6 ) + •2Cl − •H 2 O (245 nm), 47 and (H 7 C 3 N 6 )(H 6 C 3 N 6 )-ZnCl 3 (236 nm).…”
Section: Differential Thermal Analysis and Thermogravimetricsupporting
confidence: 82%
“…The possible reasons why GZCO has such a high thermal stability may include (i) GZCO is anhydrous. Generally, the hydrated crystals such as C­(NH 2 ) 3 ] 3 AsO 4 ·2H 2 O (95 °C), [C­(NH 2 ) 3 ] 6 (PO 4 ) 2 ·3H 2 O (100 °C), KLi­(HC 3 N 3 O 3 )·2H 2 O (125 °C), and 2­(C 3 H 7 N 6 ) + ·2Cl – ·H 2 O (95 °C) easily release water molecules at ∼100 °C. Because GZCO is anhydrous, its initial thermal stability is not determined by the loss of water molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to confirm this fact, DFT calculations on the dipole moments of D-1 and D-2 were performed using the Gaussian 09 package, and the results unveil that the dipole moment ( μ total = 7.14 D) of D-1 is much larger than that of D-2 ( μ total = 2.73 D) (Table S7†). Moreover, as shown in Table 1, the SHG intensities of D-1/L-1 are much larger than those of most reported SHG-active complexes, such as 1D chiral Cu( ii ) enantiomers with L R /L S ligands, 81 [Dy(dma) 5 ][W(CN) 8 ], 110 chiral R / S -FeNb enantiomers, 111 chiral YbZn 2 enantiomers, 112 chiral L/D-ZnBr 3 enantiomers, 113 (CASD) 2 MnBr 4 , 114 [(DPA)(18-crown-6)]ClO 4 , 115 chiral 2D Ag( i ) enantiomers, 80 a chiral Cu( i ) complex, 116 N*[MnCr], 117 C 2 H 10 N 2 ·Mg(H 2 PO 3 ) 2 (C 2 O 4 ), 118 [C(NH 2 ) 3 ] 2 Zn(CO 3 ) 2 , 119 ionic 1D chiral Cu( ii ) enantiomers with L R /L S ligands, 72 [Cd(en)-(1,3-dap)][AlB 5 O 10 ], 120 (morpholinium) 2 Cd 2 Cl 6 , 121 (C 4 H 10 NO)PbBr 3 , 122 [C(NH 2 ) 3 ] 3 AsO 4 ·2H 2 O, 123 and (Hdabco + )(CF 3 COO − ), 124 but slightly smaller than those of some complexes, such as a YbSe complex 125 and [(CH 3 ) 3 NCH 2 CHCH 2 ]FeCl 4 . 126 More remarkably, the SHG intensities of D-1/L-1 are even more than twice those of inorganic SHG-active materials, for example KTOH 127 and CKBFI.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, π-conjugated planar organic moieties have been successfully developed as potential NLO-active groups due to their large polarizability anisotropy, ultrafast response time, and infinite design probabilities. When the organic moieties act as anions, for instance, the (H x C 3 N 3 Q 3 ) (3– x )– (Q = O, S; x = 0, 1, and 2) groups have been harnessed to build many SHG crystals such as Ca 3 (C 3 N 3 O 3 ) 2 (SHG: >2 × β-BaB 2 O 4 ), KLi­(HC 3 N 3 O 3 )·2H 2 O (5.3 × KDP), RE 5 (C 3 N 3 O 3 ) (OH) 12 (RE = Y, Yb, and Lu) (2.5–4.2 × KDP), and Cs 3 Cl­(HC 3 N 3 S 3 ) (11.4 × KDP). Theoretical calculations revealed that the organic moieties dominate the SHG effects of these materials. The organic groups can also function as cations, for example, the [C­(NH 2 ) 3 ] + group has been widely used as a SHG building group as in [C­(NH 2 ) 3 ] 6 (PO 4 ) 2 ·3H 2 O (3.8 × KDP), C­(NH 2 ) 3 SO 3 F (5 × KDP), and [C­(NH 2 ) 3 ] 2 [B 3 O 3 F 4 (OH)] (1.4 × KDP). , It is noticed that the pyridine and pyrimidine derivative groups featuring nitrogen-containing heteroaromatic rings could be protonated and used to build organic–inorganic hybrid SHG crystals such as [ o -C 5 H 4 NHOH] 2 [I 7 O 18 (OH)]·3H 2 O (8.5 × KDP), (C 5 H 6 ON) + (H 2 PO 4 ) − (3 × KDP), and (C 4 H 6 N 3 ) + (H 2 PO 3 ) − (2 × KDP). ,, …”
Section: Introductionmentioning
confidence: 99%